2004
DOI: 10.1177/0193945904267699
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Patient Pain in the Postoperative Context

Abstract: Because of its subjective nature, the assessment of pain requires the use of comprehensive practices that accurately reflect a patient's experiences of pain. The purpose of this study was to determine how nurses make decisions in their assessment of patients' pain in the postoperative clinical setting. An observational design was chosen as the means of examining pain activities in two surgical units of a metropolitan teaching hospital in Melbourne, Australia. Six fixed observation times were selected. Each 2-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 31 publications
5
31
0
7
Order By: Relevance
“…This may indicate that patients lack either knowledge that having pain has detrimental effects on their recovery or confidence to raise their pain issue with the nurse. This finding has also been shown in other pain literature 17 despite evidence that patient education has positive effects on pain management outcomes, such as the postoperative pain experience and the patients' sense of satisfaction and control with pain management. 31,32 Interestingly, the patients who initiated reassessment were having increasing pain at the time not related to the surgical wound.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This may indicate that patients lack either knowledge that having pain has detrimental effects on their recovery or confidence to raise their pain issue with the nurse. This finding has also been shown in other pain literature 17 despite evidence that patient education has positive effects on pain management outcomes, such as the postoperative pain experience and the patients' sense of satisfaction and control with pain management. 31,32 Interestingly, the patients who initiated reassessment were having increasing pain at the time not related to the surgical wound.…”
Section: Discussionsupporting
confidence: 76%
“…Other themes are reported separately elsewhere. 16,17 Medication charts were audited for type of analgesic, dose, route, and time of administration.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is evidence to suggest that several sources of information may influence clinical decision‐making (e.g., McCaughan et al. 2002, 2005, Bucknall 2003, Manias et al. 2004b, Hancock & Easen 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Patients often arrived at a new NRS score by comparing their worst previous pain experience with the current pain sensation (Dionne et al 2005, Manias, Bucknall & Botti 2004). In the current study, we found that the NRS scores from 0 to 10 can conceal real differences in pain intensity across patients, because previous pain experiences differ between patients.…”
mentioning
confidence: 99%